Quality of the documentation of the Nursing process in clinical decision support systems - Neurilene Batista de Oliveira; Heloísa Helena Ciqueto Peres (Universidade de São Paulo, 2021)
Objective: to compare the quality of the Nursing process documentation in two versions of a clinical decision support system. Method: a quantitative and quasi-experimental study of the before-and-after type. The instrument used to measure the quality of the records was the Brazilian version of the Quality of Diagnoses, Interventions and Outcomes, which has four domains and a maximum score of 58 points. A total of 81 records were evaluated in version I (pre-intervention), as well as 58 records in version II (post-intervention), and the scores obtained in the two applications were compared. The interventions consisted of planning, pilot implementation of version II of the system, training and monitoring of users. The data were analyzed in the R software, using descriptive and inferential statistics. Results: the mean obtained at the pre-intervention moment was 38.24 and, after the intervention, 46.35 points. There was evidence of statistical difference between the means of the pre- and post-intervention groups, since the p-value was below 0.001 in the four domains evaluated. Conclusion: the quality of the documentation of the Nursing process in version II of the system was superior to version I. The efficacy of the system and the effectiveness of the interventions were verified. This study can contribute to the quality of documentation, care management, visibility of nursing actions and patient safety.